Communication: One-photon phase control of cis-trans isomerization in retinal (2013)
We computationally demonstrate the one-photon phase control of retinal isomerization under conditions of low laser intensity. The calculations, utilizing the multiconfigurational time dependent Hartree method, include coupling between the two modes that are active in isomerization and the background molecular vibrational environment. Noting previously unsuccessful computations highlights the significance of this result.